O escudo de Aquiles: o fim da Ilíada e o começo da pólis - Silva, Abigail Britto da (2024)
This work aims to make a literary analysis of the representation of the scenes present in the construction of the images forged on the shield of Achilles in book 18 in the Iliad of Homer. The Iliad is an epic that narrates a period of the Trojan War, but at one point in the narrative the poet lingers on narrating a splendid, yet complex feat in divine metallurgy: the scenes of a world and its characters. For the analysis, we propose a comparison between the thematic elements of the description of the shield and Polis. The study begins with the representation of the hero's epic context, then will rest on the context of Polis, in the 8th century BC., time attributed to Homer. The composition of this episode is found in verses 468-608 in book 18 of the Iliad: shield of Achilles is forged by Hephaestus with five layers of metal that bear images of the elements of nature and the current life of a community. Therefore, we made a possible counterpoint to establish a link of receptions of themes known to his audience, in which the poet, in addition to the imaginary, gives an archaic and realistic touch to his epic. For educational purposes, we will also bring an operational translation of ours with the Greek text. Among the theorists covered in our study, we adopted as a basis, in reception, Carvalhal (2006) and, in the context of the Iliad, Hesiod (2011); Aubreton (1968); Aristotle (2005; 2015); Vernant and Vidal-Naquet (2008); Vernant (1990; 1999). And to make reference to the historical part of the poet, we chose to use Vidal-Naquet (2002); Graziosi (2022). We therefore considered other theorists so that we could apply approaches with the aim, as far as possible, of supporting the narrative of the decorations on Achilles' shield.